PENGEMBANGAN SMART EDIBLE PACKAGING BERBAHAN ALGINAT DENGAN PENAMBAHAN EKSTRAK BUNGA TELANG DAN TEPUNG CANGKANG TELUR AYAM - Michellyn Alvina; Rachel Meiliawati Yoshari; Jati, Ignasius Radix A.P. (Fakultas Pertanian Universitas Alkhairaat Palu, 2024)
Smart edible packaging is a type of packaging that includes smart agents and can be made using alginate, chicken eggshell flour and butterfly pea flower extract. The smart agents added to the packaging help to increase its sturdiness, elasticity, and ability to detect and respond to changes in the quality of the packaged products. The purpose of the study was to investigate the physicochemical properties and capabilities of smart edible packaging as a food packer. The data collected was analyzed using ANOVA (α = 5%) and continued with the DMRT test (α = 5%). The results showed that there is an interaction between the concentration of chicken eggshell flour and the ratio of butterfly pea flower extract, which has a significant effect on tensile strength factors (2.9227-12.1723N/mm2), % elongation (18.02-40.7733%), and WVTR (96.9625-203.9756g/m2/24 hours) in smart edible packaging. However, the total anthocyanin factor (0.1364-3.0757mg cy-3-glu eq/100g ingredient), total phenol (158.8844-998.0301mg GAE/100g ingredient), and antioxidant activity (4.1734-90.6775%) were only influenced by the concentration of butterfly pea flower extract. The study found that the use of smart edible packaging, specifically treatment T3, can help maintain the quality of chicken meat during storage.